Konsep Good Governance Lembaga Pengelola Zakat - Hasibuan, Indra Mualim; Juliati Nasution, Yenni Samri (AKTIVA: Journal of Accountancy and Management, 2024)
Research Purposes: This research aims to determine the application of good governance principles in zakat institutions accompanied by concrete evidence that has been implemented by zakat management institutions in Indonesia.Design, Methodology, Approach: This research is library research, data sources are obtained from journals, books and other documents.Research Findings: good governance principles that can be implemented by zakat institutions include: the principles of transparency, accountability, responsibility, independence and justice, as an effort to increase the professionalism of zakat institutions while increasing muzakki's trust in zakat management institutions. . Concrete evidence of the application of good governance principles has been actualized by many zakat management institutions in Indonesia, both Baznas and Laznas.Research Contribution: research provides new insights related to the implementation of good governance by zakat management institutions Tujuan Penelitian: Penelitian ini bertujuan untuk mengetahui penerapan prinsip good governance pada lembaga zakat disertai dengan bukti nyata yang telah diterapkan oleh lembaga pengelola zakat di Indonesia.Desain, Metodologi, Pendekatan: Penelitian ini merupakan penelitian kepustakaan, sumber data diperoleh dari jurnal, buku dan dokumen lainnya.Temuan penelitian: prinsip-prinsip good governance yang dapat diterapkan oleh lembaga zakat antara lain: prinsip transparansi, akuntabilitas, responsibilitas, independensi dan keadilan, sebagai upaya meningkatkan profesionalisme lembaga zakat sekaligus meningkatkan kepercayaan muzakki terhadap lembaga pengelola zakat. Bukti nyata penerapan prinsip good governance telah diaktualisasikan oleh banyak lembaga pengelola zakat di Indonesia, baik Baznas maupun Laznas.Kontribusi Penelitian: penelitian memberikan wawasan baru terkait dengan penerapan good governance lembaga pengelola zakat